Left atrial spontaneous echo contrast: relationship with clinical and echocardiographic parameters - Takahide Ito; Michihiro Suwa (Echo Research and Practice, 2019)
Spontaneous echo contrast (SEC) indicates blood stasis in cardiac chambers and major vessels, and is a known precursor of thrombus formation. Transesophageal echocardiography plays a pivotal role in detecting and grading SEC in the left atrial (LA) cavity. Assessing LA SEC can identify patients at increased risk for thromboembolic events. LA SEC also develops in patients who have sinus rhythm, especially in those with heart failure. Detection of LA SEC is not uncommon in subjects who have multiple cardiovascular comorbidities, although mechanisms behind this association are not fully understood. In patients with atrial fibrillation, the role of mitral regurgitation in counteracting LA SEC and subsequent thromboembolism is controversial. Moreover, alterations of blood coagulability and elevated levels of certain biological markers in the blood contribute to occurrence of LA SEC. This review describes the pathogenesis and assessment of SEC, in addition to the relationship between LA SEC and clinical, biological and echocardiographic parameters.